The role of the pathologist in the design and conducting of biomarker-driven clinical trials in cancer: position paper of the European Society of Pathology - Matias-Guiu, Xavier; Raspollini, Maria Rosaria; Kulka, Janina; Ryska, Ales; Al Dieri, Raed; Schirmacher, Peter (Virchows Archiv, 2025)
Clinical trials in oncology are important tools to identify and establish new effective drugs for cancer treatment. Since the development of the concept of precision oncology, a huge number of multi-centric biomarker-driven clinical trials have been performed and promoted by either academic institutions or pharmaceutical companies. In this scenario, the role of pathologists is essential in multiple aspects, with new challenges that should be addressed. In this position paper of the European Society of Pathology, the role of pathologists as contributors to the design of the clinical trial, as local collaborators, or as members of central review laboratories is discussed. Moreover, the paper emphasizes the important role of pathologists in guiding methods and criteria of tissue biomarker testing in the biomarker-driven clinical trials. The paper also addresses issues regarding quality control, training, and the possible role of digital pathology.
Online veröffentlicht: 17. Dezember 2024
Gesehen am 04.06.2025